2016
DOI: 10.1007/s12010-016-2200-y
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Mobility: a Paradigm for Protein Engineering?

Abstract: Additional Information:Question ResponsePlease select a section/category for your manuscript.Biocatalysis for organic synthesis -Novel and significant advances in biocatalysis for organic synthesis, including chemo-, regio-and enantioselective biotransformation, screening and engineering of novel enzymes for biocatalysis, biocatalyst immobilization, and nonaqueous biocatalysis.Abstract: Proteins are highly mobile structures. In addition to gross conformational changes occurring on, for example, ligand binding,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…The flexibility of protein residues is often associated with enzyme stability (McAuley & Timson, 2016). It has been suggested that the stability of lipases is due to their conformation being more rigid in organic solvents (Sharma & Kanwar, 2014).…”
Section: Residue Flexibilitymentioning
confidence: 99%
“…The flexibility of protein residues is often associated with enzyme stability (McAuley & Timson, 2016). It has been suggested that the stability of lipases is due to their conformation being more rigid in organic solvents (Sharma & Kanwar, 2014).…”
Section: Residue Flexibilitymentioning
confidence: 99%
“…We pay special attention to how these modifications can generate stimulus‐responsive enzymes (e.g., light‐activated), providing unique biotechnology tools. We note that our examples are illustrative, not exhaustive, and that there are other recent reviews related to this area that may highlight alternative cases or approaches …”
Section: Introduction: the Case For Dynamicsmentioning
confidence: 99%
“…We note that our examples are illustrative, not exhaustive, and that there are other recent reviews related to this area that may highlight alternative cases or approaches. [8][9][10][11][12][13] Enzyme Structural Dynamics and the Chemical Step…”
mentioning
confidence: 99%
“…Because each step of enzymatic reaction has a value of activation energy significantly lower than the value of activation energy for the same chemical reaction, enzymes can increase a rate of reaction 10 6 -10 18 folds. According to contemporary hypothesis, high conformational mobility of the enzymes allows them to adopt their active sites to substrate(s) and intermediates of the reaction in the best way [1,2]. Multiple conformers of enzymes with close values of free energy preexist in the solution simultaneously.…”
Section: Introductionmentioning
confidence: 99%